2012
DOI: 10.1089/aid.2010.0311
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator Activating Receptor Alpha and Gamma Polymorphisms and Metabolic Abnormalities in HIV-Infected Patients Receiving Highly Active Antiretroviral Therapy: The ANRS CO8 APROCO-COPILOTE Study

Abstract: Highly active antiretroviral therapy (HAART) is associated with fat redistribution and metabolic disorders. The present study was undertaken to evaluate the association between peroxisome proliferator activated receptor (PPAR)α and PPARγ polymorphisms, two genes involved in lipid metabolism and adipocyte differentiation, and elements of the metabolic syndrome, lipodystrophy, or carbohydrate metabolism abnormalities in patients receiving HAART. The frequency distribution of rare alleles for PPARα (L162V) and PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…72 The effects on lipid metabolism were also suggested by a sub-analysis of a prospective cohort study on HIV-infected individuals on PI-based regimens, which found an association between PI-related lipodystrophy and diminished levels of peroxisome proliferator activator receptor-gamma (PPAR-gamma), which regulate genes involved in lipid homeostasis and inflammation. 74 These findings were supported by an in-vitro study on human and murine adipocytes, which found that PPAR-gamma agonist exposure attenuated PI-induced RAAS activation but that PPAR antagonists increased RAAS activation. 24 The relationship between PPAR-gamma and RAAS has been extensively explored in the general population using murine models of dominant negative mutations of PPAR-gamma, which are associated with hypertension in humans.…”
Section: Mechanismsmentioning
confidence: 81%
“…72 The effects on lipid metabolism were also suggested by a sub-analysis of a prospective cohort study on HIV-infected individuals on PI-based regimens, which found an association between PI-related lipodystrophy and diminished levels of peroxisome proliferator activator receptor-gamma (PPAR-gamma), which regulate genes involved in lipid homeostasis and inflammation. 74 These findings were supported by an in-vitro study on human and murine adipocytes, which found that PPAR-gamma agonist exposure attenuated PI-induced RAAS activation but that PPAR antagonists increased RAAS activation. 24 The relationship between PPAR-gamma and RAAS has been extensively explored in the general population using murine models of dominant negative mutations of PPAR-gamma, which are associated with hypertension in humans.…”
Section: Mechanismsmentioning
confidence: 81%
“…Indeed, some promising therapeutic effects were observed in phase II trial of Tat vaccine. 8,9 A number of chronic metabolic abnormalities including disorders of lipid metabolism with or without lipodystrophy, 10 insulin resistance, 11 cardiometabolic syndrome, 11 altered phosphate metabolism, 12 and an increased prevalence of impaired glucose tolerance 13 are found prevalent in HIV patients with or without receiving highly active antiretroviral therapy (HAART). Although multiple risk factors have been proposed, the etiology of these metabolic abnormalities remains unclear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This meta-analysis suggests that, compared with rs1801282 CC genotype, carriers of rs1801282 CG/GG genotype have significant increased blood TC, and marginally significant increased blood HDL-C in healthy male subjects [ 16 ]. Moreover, there are only three articles published about PPARγ2 rs1801282 polymorphism in HIV infection [ 37 39 ], which did not find any association of rs1801282 polymorphism with lipodystrophy, lipid profile, and insulin sensitivity in HIV-1-infected patients treated with cART [ 37 39 ]. In our HIV/HCV coinfected patients, Ala variant carriers had lower values of TC, LDL-C, LDL-C/HDL-C, and AI.…”
Section: Discussionmentioning
confidence: 99%